Kontribusi Guru Pendidikan Pancasila dan Kewarganegaraan Dalam Memperbaiki Akhlak Peserta Didik - Azizah Fatwa Azzahra; Murniyetti Murniyetti (Prodi Pendidikan Keagamaan Islam, 2022)
The purpose of this study was to find out how the contribution of Civics teachers in improving the morals of grade 1 students at SDN 07 Sintuk Toboh Gadang, using a qualitative case study method. The data was collected using interview, observation, and documentation methods, then analyzed by collecting, reducing, presenting, and drawing conclusions. Techniques to test the validity of the data include an extension of participation, persistence of observation, and triangulation. The results of the study show that: first, only some of the first-grade students have bad morals. Second, the contributions of Civics teachers include: participating in Qur'an memorization murojaah activities, changing seats, visiting sick friends, carrying out Goro activities, and class pickets. Third, the supporting and inhibiting factors are heredity and the environment, this can be a supporting factor as well as an inhibiting factor in improving the morals of grade 1 students at SDN Sintuk Toboh Gadang.